Predictive Performance of Physiology‐Based Pharmacokinetic Dose Estimates for Pediatric Trials: Evaluation With 10 Bayer Small‐Molecule Compounds in Children. (29th June 2021) - Ince, Ibrahim; Dallmann, André; Frechen, Sebastian; Coboeken, Katrin; Niederalt, Christoph; Wendl, Thomas; Block, Michael; Meyer, Michaela; Eissing, Thomas; Burghaus, Rolf; Lippert, Jörg; Willmann, Stefan; et al.
Abstract: Development and guidance of dosing schemes in children have been supported by physiology‐based pharmacokinetic (PBPK) modeling for many years. PBPK models are built on a generic basis, where compound‐ and system‐specific parameters are separated and can be exchanged, allowing the translation of these models from adults to children by accounting for physiological differences. Owing to these features, PBPK modeling is a valuable approach to support clinical decision making for dosing in children. In this analysis, we evaluate pediatric PBPK models for 10 small‐molecule compounds that were applied to support clinical decision processes at Bayer for their predictive power in different age groups. Ratios of PBPK‐predicted to observed PK parameters for the evaluated drugs in different pediatric age groups were estimated. Predictive performance was analyzed on the basis of a 2‐fold error range and the bioequivalence range (ie, 0.8 ≤ predicted/observed ≤ 1.25). For all 10 compounds, all predicted‐to‐observed PK ratios were within a 2‐fold error range (n = 27), with two‐thirds of the ratios within the bioequivalence range (n = 18). The findings demonstrate that the pharmacokinetics of these compounds was successfully and adequately predicted in different pediatric age groups. This illustrates the applicability of PBPK for guiding dosing schemes in the pediatric population.